Synthesis of tricarbonylated propargylamine and conversion to 2,5-disubstituted oxazole-4-carboxylates - Kento Iwai; Akari Hikasa; Kotaro Yoshioka; Shinki Tani; Kazuto Umezu; Nagatoshi Nishiwaki (Beilstein Journal of Organic Chemistry)
The N,O-acetal derived from diethyl mesoxalate (DEMO) undergoes elimination of acetic acid upon treatment with a base, leading to the formation of N-acylimine in situ. Lithium acetylide readily attacks the imino group to afford N,1,1-tricarbonylated propargylamines. When the resulting propargylamine reacts with butyllithium, ring closure occurs between the ethynyl and carbamoyl groups, yielding 2,5-disubstituted oxazole-4-carboxylates. This cyclization also occurs when the propargylamine is heated with ammonium acetate, resulting in double activation.